2020
DOI: 10.3389/fpsyt.2020.00428
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an Own-Age Bias in Facial Emotion Recognition for Adolescents With and Without Autism Spectrum Disorder

Abstract: A common interpretation of the face-processing deficits associated with autism spectrum disorder (ASD) is that they arise from a failure to develop normative levels of perceptual expertise. One indicator of perceptual expertise for faces is the own-age bias, operationalized as a processing advantage for faces of one's own age, presumably due to more frequent contact and experience. This effect is especially evident in domains of face recognition memory but less commonly investigated in social-emotional experti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…However, Luo et al [ 26 ] showed that this effect dissipates by 4.5 years of age, which is younger than the faces used for the present study. The use of child faces could also impact the findings by facilitating children’s performance; a recent study of adolescents revealed an own-age bias in emotion recognition [ 27 ]. Another potential limitation is the inclusion of only emotionally ambiguous neutral faces.…”
Section: Discussionmentioning
confidence: 99%
“…However, Luo et al [ 26 ] showed that this effect dissipates by 4.5 years of age, which is younger than the faces used for the present study. The use of child faces could also impact the findings by facilitating children’s performance; a recent study of adolescents revealed an own-age bias in emotion recognition [ 27 ]. Another potential limitation is the inclusion of only emotionally ambiguous neutral faces.…”
Section: Discussionmentioning
confidence: 99%
“…This list is typically limited to words representing four to six basic (universal) emotion categories (i.e. happy sad, angry, fearful, disgust, surprise) (Airdrie et al, 2018;Grosbras et al, 2018;Hauschild et al, 2020;Melendez et al, 2020;Zupan & Babbage, 2017). This format permits ease of analysis, reproducibility, and comparison across studies but also constrains responses, potentially resulting in artificial and inflated agreement among participants (Barrett et al, 2011;Limbrecht-Ecklundt et al, 2013;Nelson & Russell, 2013) and masking nuances in how people conceptualise and interpret emotion (Turkstra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was supported by the study of Hauschild, indicating that adolescents, independently of ASD diagnostic status or severity of troubles had greater FER performance for child compared to adult faces. His findings suggested that “face processing abilities of adolescents with ASD may be influenced by experience with specific categories of stimuli, similar to their typically developing peers” ( 28 ). Therefore, we hypothesized that children with ASD would show greater performance in recognizing facial emotions of individuals having the same age range and that the assessment of facial emotion recognition could vary according to the age range of the model presented to the child.…”
Section: Introductionmentioning
confidence: 99%